The Effect of Flexitime on Job Performance and Family-Work Conflict: A Study of Employees in Batam with a Focus on Ability to Cope - Agostinan, Kifnisa Bella; Mon, Muhammad Donal (Celebes Scholar pg, 2025)
This study aims to analyze the effect of flexitime on job performance and family-work conflict, as well as the mediating and moderating roles of family-work conflict and ability to cope among industrial employees in Batam. This study used a quantitative approach with a purposive sampling technique and involved 267 respondents from five manufacturing companies in the Batamindo Industrial Estate. Data were collected through questionnaires and analysed using SmartPLS 4.0. The results showed that flexitime had a positive and significant effect on job performance and was able to reduce family-work conflict. Family-work conflict had a negative effect on job performance and was proven to mediate the relationship between and job performance, but was not significant in the relationship between flexitime and family-work conflict. This study provides implications that the effective implementation of flexitime and strengthening employee coping abilities can improve performance and reduce role conflict in organizations.